"80% of technical information found only in patents" – Is there proof of this [1]?. (March 2017) - Asche, Geert
Abstract: "80% of technical information is published only in patents". This sentence is well known among information and patent professionals. Within this publication the commonly considered source of this statement is cited and examples of different published patent statistics are given, illustrating previous approaches of quantifying information. Prospects for the importance of patent literature are provided considering the rising number of patent publications over the last decades. The conclusion of this verification is that the 80%-phrase cannot be used without making some limitations, nevertheless this will continue existing for a long period of time.